Wages and Health Worker Retention in Ghana : Evidence from Public Sector Wage Reforms - Antwi, James (World Bank, Washington, DC, 2013)
Can governments in developing countries retain skilled health workers by raising public sector wages? The author investigates this question using sudden, policy-induced wage variation, in which the Government of Ghana restructured the pay scale for government health workers. The author find that a ten percent increase in wages decreases annual attrition from the public payroll by 1.5 percentage points (from a mean of eight percentage points) among 20-35 year-old workers from professions that tend to migrate. As a result, the ten-year survival probability for these health workers increases from 0.43 to 0.52. The effects are concentrated among these young workers, and we do not detect effects among older workers or among categories of workers that do not tend to migrate. Given Ghana's context as a major source of skilled health professional migrants and high correlation of our attrition measure with aggregate migration, the author interpret these results as evidence that wage increases in Ghana improve retention mainly through reducing international migration.